EVALUATION OF NUTRIENT LOAD AND TROPHIC STATUS OF LOTIC ENVIRONMENTS IN CHANDRAPUR, MAHARASHTRA - PAYAL M. BAMBOLE; KAVITA S. RAIPURKAR (The Bioscan, 2025)
Erai and Zarpat rivers, flows through the Chandrapur city and are lifelines of Chandrapur. Increasing anthropogenic activities within the catchment of these rivers influencing their water quality. Identifying the key nutrients responsible for eutrophication is important for proper management of watersheds. Total 70 water samples from 14 locations were collected for nutrient analysis to evaluate nutrient loading particularly due to nitrogen and phosphorus and dissolved silica to investigate DIN/DIP and DSi/DIN ratios.DIN/DIP ratio estimates the limiting factor and growth of phytoplankton was estimated by DSi/DIN ratio. DIN/DIP ratio of Erai river was 4:1 indicating phosphate limiting condition and DSi/DIN ratio was 5:1 indicating phytoplankton growth specially diatoms. For Zarpat River DIN/DIP ratio was 3:1 indicating phosphate limiting condition and DSi/DIN ratio 3:1 indicated phytoplankton growth especially due to diatoms. Authors come to the conclusion that phosphorus is the principal limiting nutrient controlling river eutrophication and DSi/DIN ratio showed the planktonic growth in both the rivers. Erai river showed enriched nutrient status for TSI (Chl a) and showed in the downstream region mesotrophic to hyper-eutrophic conditions and river Zarpat showed mesotrophic to eutrophic in upstream areas. TSI for TP of both the rivers showed hyper-eutrophic TSI confirming eutrophication conditions.